2021
DOI: 10.2147/jpr.s309729
|View full text |Cite
|
Sign up to set email alerts
|

More Insight on the Role of Personality Traits and Sensitivity to Experimental Pain

Abstract: Purpose The present study aimed to assess the influence of personality traits on the variability of sensitivity to pain in two distinct groups of healthy subjects with low versus high sensitivity to pain (LSP vs HSP, respectively). Methods Healthy subjects (n=156) were allocated to two groups according to their tolerability to cold stimulation (cold pressor test, CPT, 1°C). Group LSP (n=76) reached the cut-off time of 180±0 sec, and a size matched group of HSP (n=80) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…In addition, we found that PCS and CHPASS scores correlated negatively with the current intensity, suggesting that higher levels of pain-related emotions and cognition render subjects more sensitive to pain, reducing the current intensity required to achieve the same pain score. The effects of pain-related catastrophic thinking and anxiety on pain sensitivity have been demonstrated in many studies (Failla et al, 2020;Grouper et al, 2021;Kim et al, 2021). Taken together, the significant correlations observed in this study between the current intensity and the PSE and PCS and CHPASS scores suggest that the impacts of pain-related cognitive, emotional, and sensory factors on time perception may be direct and/or indirect.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, we found that PCS and CHPASS scores correlated negatively with the current intensity, suggesting that higher levels of pain-related emotions and cognition render subjects more sensitive to pain, reducing the current intensity required to achieve the same pain score. The effects of pain-related catastrophic thinking and anxiety on pain sensitivity have been demonstrated in many studies (Failla et al, 2020;Grouper et al, 2021;Kim et al, 2021). Taken together, the significant correlations observed in this study between the current intensity and the PSE and PCS and CHPASS scores suggest that the impacts of pain-related cognitive, emotional, and sensory factors on time perception may be direct and/or indirect.…”
Section: Discussionsupporting
confidence: 71%
“…To date, no evidence could be found for a dog's temperament to influence its pain behaviour [38]. This is in contrast to findings in humans, in which personality traits like catastrophizing, extraversion and neuroticism have been associated with an increased sensitivity to pain [39]. One explanation might be the different scoring methods between self-reporting in people and observer-reporting in animals.…”
Section: Factors Influencing Sedation and Pain Scoresmentioning
confidence: 78%
“…There is a growing interest into investigating whether ongoing, painful clinical conditions can be attributed to the personality of the sufferer (Bar‐Shalita & Cermak, 2019; Clark et al., 2017; Grouper et al., 2021). Therefore, a third panel, consisting of nine patients suffering from recurring or ongoing painful conditions and undergoing treatment at an out‐patient clinic, was recruited to independently review and fill out the questionnaire.…”
Section: Methodsmentioning
confidence: 99%